สถานภาพความต้องการและแนวโน้มการเรียนรู้ตลอดชีวิต ของกลุ่มคนหลายวัยในจังหวัดนครสวรรค์: Predicament of Needs and Lifelong Learning Trends of Various Ages People in Nakhon Sawan Province - Siribhorn Semathong สิริพร เสมาทอง; Wudhijaya Philuek วุฒิชัย พิลึก (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2023)
The purpose of this research was to analyze the status, needs and lifelong learning trends of various ages people in Nakhon Sawan Province which was the mixed research method by synthesis documents, theories, and related research about lifelong learning. Data resource were documents, theories, and related research papers on lifelong during 2556-2565 B.E. The target group was school age group, working age group, and elderly people with totally 550 persons. This research was survey research which conducted between July 2022 to October 2022 by using survey research techniques. Tools used to collect information include: a survey of lifelong learning needs of students, working age people, and elderly people, courses that want to study in Upskill/Reskill with the reliability at 0.82. Data were collected by online questionnaire. Quantitative data were analyzed using basic statistics such as Percentage, Mean and Standard Deviation. The results showed that, demand status and lifelong learning trends were as follows: 1) Children and youth outside the formal education system have important guidelines that are (1) flexibility according to the context of the learners, (2) emphasizing individual differences of learners, (3) livelihoods and occupations, (4) participation. of all sectors in education management, and (5) promoting lifelong learning of learners. 2) The students had the following educational management styles: Model 1, students experienced work experience; Model 2, students gained work experience and learned the real working world; and Model 3, students delivered value to the workplace. 3) The format of the curriculum for the working age is as follows: (1) a curriculum that emphasizes knowledge and skills using advanced technology; (2) a curriculum that emphasizes knowledge and skills for middle and basic workers; and (3) a short-term learning curriculum. according to the interests of the students, and 4) The elderly have 2 forms: (1) learning for life (2) learning for work and the results of the survey of people of different ages found that most of target group have a need and tendency for lifelong learning both in the formal and non-formal in subjects: the ecosystem aspect of labor skill development was needed at the highest level, followed by 7C skills was needed at the highest level.